Solid lipid nanoparticles as an effective sodium aescinate delivery system: formulation and anti-inflammatory activity. Issue 11 (24th February 2022) - Wang, Jinyue; Wang, Hongyue; Xu, Hongjia; Li, Jinghan; Zhang, Xu; Zhang, Xiangrong
Abstract : Solid lipid nanoparticles (SLNs) to encapsulate sodium aescinate (SA) were prepared by a double emulsion (DE) technique. SLNs were optimized by orthogonal and Box–Behnken designs. SLNs – SA presented a higher anti-inflammatory activity than free SA. Abstract : Sodium aescinate-loaded solid lipid nanoparticles were fabricated using a melt-emulsification and ultrasonication method. Based on mean particle size, polydispersity index, and encapsulation efficiency, orthogonal and Box–Behnken designs were applied to optimize solid lipid nanoparticles with single emulsification and double emulsification methods. The characterization of solid lipid nanoparticles was investigated by X-ray diffractometry, differential scanning calorimetry, and scanning electron microscopy. After optimization of sodium aescinate-loaded solid lipid nanoparticles with single emulsification, the particle size was 90.7 nm and encapsulation efficiency was 76.5%. The sodium aescinate-loaded solid lipid nanoparticles with double emulsification were negatively charged spherical particles with the size of 109.4 nm and encapsulation efficiency up to 86.6%. Both solid lipid nanoparticles with single emulsification and double emulsification exhibited sustained release for 12 h without an initial burst release. The results indicated that sodium aescinate-loaded solid lipid nanoparticles by double emulsification showed more drug loading and stability after reconstitution. The sodium aescinate-solid lipid nanoparticles with double emulsification demonstrated stronger anti-inflammatory activity, including paw edema and ear swelling in mice than that of free sodium aescinate. Therefore, solid lipid nanoparticles have great potential as an effective sodium aescinate delivery system for application in medicine.